A Qualitative Impact Evaluation of the First Love Yourself (FLY) Women’s Support Group - Valerie Blackmon; Chalenna Cassell; Cathy G. McElderry; Olawunmi Obisesan (International Journal of Public Health Science (IJPHS), 2016)
Research has shown that social support groups not only have significant effects on the physical and mental health of individuals, but can also be used as predictors of health outcomes. It is, therefore, important that social workers and other public health professionals are aware of the social support groups that exist in communities so as to find ways to utilize these to meet health needs. The study aims to explore the First Love Yourself (FLY) group, an empowerment-based support group specifically designed to meet the needs of Healthy Start consumers, parents and consortium members. A qualitative analysis of the data gathered from this focus group study yielded several key themes. While participants described finding other community resources helpful, they reported having no other outlet for confidential self-expression and connection to peers other than the FLY group. Group members also reported having improved self-esteem, relationships with their children, partners, and family, and ability to cope as a result of participation in the group. Participants further described gaining knowledge and learning skills that were helpful. This included learning parenting, communication, stress and anger management, budgeting, goal-setting and coping skills and techniques. Finally, qualitative analysis of the data gained from the focus group with participants and the group leader revealed the presence of all 11 curative factors described by Yalom (2005). The primary areas for improvement noted by the group and its leader were related to the frequency of group meetings. Both audiences indicated that additional sessions would be beneficial.